2022
DOI: 10.1111/jonm.13593
|View full text |Cite
|
Sign up to set email alerts
|

Business acumen for nursing leaders: A scoping review

Abstract: Aim The aim of this study is to explore the current evidence on business acumen of nurse leaders. Background Health systems across the world are under immense pressure to stay solvent, maintaining services within a defined budget as we recover from the COVID‐19 pandemic. Effective nurse leaders not only need to have strong leadership and management skills but also strong business acumen to navigate the complexity of the system. Evaluation A scoping review of research was undertaken, using preferred reporting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our study found a significant difference between the position of nurses, the clinic they worked in, and their scores on the ‘being energetic’ subscale. Nurses in leadership roles often juggle increased autonomy and responsibilities (Fida et al, 2018), demanding heightened energy and enthusiasm to ensure quality patient care (Raftery et al, 2022). Drawing from their extensive professional experiences, Generation X nurses might better navigate these demands, mirrored in their higher ‘energy’ scores.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a significant difference between the position of nurses, the clinic they worked in, and their scores on the ‘being energetic’ subscale. Nurses in leadership roles often juggle increased autonomy and responsibilities (Fida et al, 2018), demanding heightened energy and enthusiasm to ensure quality patient care (Raftery et al, 2022). Drawing from their extensive professional experiences, Generation X nurses might better navigate these demands, mirrored in their higher ‘energy’ scores.…”
Section: Discussionmentioning
confidence: 99%
“…“Interrelating” is deemed important for the functioning of boards (Forbes and Milliken, 1999), but this is mostly approached as a dynamic within boards or as an interaction with other agents regarding boards’ direct tasks (Carroll et al , 2017; Kane et al , 2009), such as decision-making. How BM relate and how they manage the interdependency with agents outside of the board remains scarce in research (Boivie et al , 2021) but can be a valuable avenue regarding the previously mentioned pressures of board accountability and the development of professionalism (Noordegraaf, 2020; Raftery et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Through a recent scoping review by the authors, only 17 research studies were on the business acumen of nursing leaders from the past decade (Raftery et al, 2022). Across the health literature, leadership and management research is well covered.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies discussed challenges to the need and value of passively accessing foundation business education throughout one's clinical career or applying these skills as nurse leaders across health systems. What was also evident across the papers was that what business acumen in healthcare entailed was not consistent or clearly defined (Raftery et al, 2022).…”
Section: Introductionmentioning
confidence: 99%